2022
DOI: 10.1071/rd22184
|View full text |Cite
|
Sign up to set email alerts
|

Association between

Abstract: Context The number of women who achieve pregnancy through assisted reproductive technology (ART), including in vitro fertilisation and embryo transfer (IVF-ET), is increasing worldwide. Placenta-mediated diseases associated with ART, such as gestational hypertension, preeclampsia, disorders of placental implantation, and placental abruption, are also increasing. Aims To determine the association between placental pathologies and IVF-ET in women with preterm births. Methods This retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 33 publications
0
4
3
Order By: Relevance
“…Other reports on the impact of ROS on embryo quality implied that an increase in the rate of ROS in ICSI cycles is associated with an increase in the rate of embryo fragmentation (>10%) [33,[57][58][59][60][61]. However, our study showed no association between MDA levels in the embryo surrounding and embryo fragmentation.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Other reports on the impact of ROS on embryo quality implied that an increase in the rate of ROS in ICSI cycles is associated with an increase in the rate of embryo fragmentation (>10%) [33,[57][58][59][60][61]. However, our study showed no association between MDA levels in the embryo surrounding and embryo fragmentation.…”
Section: Discussioncontrasting
confidence: 78%
“…However, our study showed no association between MDA levels in the embryo surrounding and embryo fragmentation. Embryo fragmentation is defined by the appearance of anucleated fragments in the cytoplasm during the cleavage stage [61,62,59,63]. Although it is a common feature of IVF-derived embryos [64][65][66][67], the mechanisms and causes of embryo fragmentation are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The association between pruritus and depression (5)(6)(7)(8), anxiety (7,8), insomnia (6,(9)(10)(11) and quality of life (QoL) (12,13) has been demonstrated previously in many studies. However, earlier reports have focused mostly on selected patient samples, such as those from dermatology or specified pruritus clinics (6,8) or specific patient groups (e.g. renal patients with pruritus) (14), whereas general population studies concerning the association with pruritus and psychosocial well-being are scarce (1).…”
Section: Significancementioning
confidence: 81%
“…Pruritus is a distressing symptom with extensive impact on functional, social and psychosocial behaviour (4). The association between pruritus and depression (5)(6)(7)(8), anxiety (7,8), insomnia (6,(9)(10)(11) and quality of life (QoL) (12,13) has been demonstrated previously in many studies. However, earlier reports have focused mostly on selected patient samples, such as those from dermatology or specified pruritus clinics (6,8) or specific patient groups (e.g.…”
Section: Significancementioning
confidence: 88%
See 1 more Smart Citation